Soliton Dynamics of Magnetization Driven by a Magnetic Field in Uniaxial Anisotropic Ferromagnet - Zhong-Xi Zheng (Brazilian Journal of Physics, 2006)
We study the nonlinear magnetic excitation in an anisotropic ferromagnet with a magnetic field. In the longwave approximation, the Landau-Lifschitz equation with easy axis anisotropy is transformed into the nonlinearSchr¨odinger type. By means of a straightforward Darboux transformation we obtain the one- and two-solitonsolutions of uniaxial anisotropic ferromagnet. From a careful analysis for the asymptotic behavior of twosolitonsolution we find that the collision between two magnetic solitons is elastic. This will be very helpful tounderstand the significant nature of the interactions between solitons in the future.